Factors contributing to English Language Anxiety (ELA) impacting diploma students / Nur Apriyani Abdul Razak and Ezatil Maisarah Zulhadi - Abdul Razak, Nur Apriyani; Zulhadi, Ezatil Maisarah (2024)
The purpose ofthe study was to examine the relationship factors contributing to English Language Anxiety (ELA) impacting Diploma students. The study was carried between May 2023 until February 2024. This study employed a stratified sampling techniques by using questionnaires method in collecting the survey data. The result of the study revealed four important findings. First, there is relationship between the ELA impacting Diploma students and afraid of making mistakes when speaking English. Second, there is strongly positive relationship between ELA impacting Diploma students and mother tongue interference and there is strongly positive relationship between ELA impacting Diploma students and social cultural differences. Lastly, the four main finding is majority ofthe respondents were agreed with the mother tongue interference is the most influenced factor contributing to ELA impacting Diploma students. Therefore, this studies uniquely positions itselfto make both theoretical and empirical contributions to the multi- domain literature including management and psychology literature.